Comorbidities in Children with COVID-19 and MIS-C/PIMS-TS and Risk Factors for Hospitalization, Severe Disease, Intensive Care and Death - Ankermann, Tobias; Brinkmann, Folke (Klinische Pädiatrie, 2022)
This narrative review sums up data from the SARS-CoV-2-pandemia on preexisting disease/underlying conditions/comorbidities and risk factors in children for severe COVID-19 and MIS-C/PIMS-TS as well as hospitalization and mortality. Young infants and adolescents are at highest risk of hospital and PICU admission. Two or more comorbidities rather than single entities pose a risk for more severe courses of SARS-CoV-2 infection in children. Asthma and malignancy do not increase complication rates. MIS-C/PIMS-TS is not associated with any specific underlying disease.
Keywords: COVID-19; MIS-C/PIMS-TS; children; severe disease; risk faktor; underlying disease